2012
DOI: 10.1002/mop.26633
|View full text |Cite
|
Sign up to set email alerts
|

Low‐profile, small‐size, wireless wide area network handset antenna close integration with surrounding ground plane

Abstract: An internal wireless wide area network (WWAN) handset antenna having a low profile of 3 mm, small footprint of 30 × 10 mm2, and closely integrated with surrounding ground plane is presented.The antenna volume is 0.9 cm3 only and can provide two wide‐operating bands to cover the desired 824–960 and 1710–2170 MHz bands. The major portion of the antenna is printed on the main circuit board of the handset, and the antenna has a simple structure formed by a strip monopole and a parasitic shorted strip monopole. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Therefore, the antenna's lower band can be shifted to lower frequency to cover the LTE Band17 band (704–746 MHz). Note that this tuning technique not only leads the antenna to cover the LTE operating band but also achieves a compact antenna volume similar to that of the reported WWAN handset antenna . The proposed antenna was fabricated and tested.…”
Section: Proposed Tunable Coupled‐fed Loop Antennamentioning
confidence: 89%
“…Therefore, the antenna's lower band can be shifted to lower frequency to cover the LTE Band17 band (704–746 MHz). Note that this tuning technique not only leads the antenna to cover the LTE operating band but also achieves a compact antenna volume similar to that of the reported WWAN handset antenna . The proposed antenna was fabricated and tested.…”
Section: Proposed Tunable Coupled‐fed Loop Antennamentioning
confidence: 89%
“…The wideband internal planar antenna printed on the circuit board directly is promising for applications of thin-profile mobile phones since it is easy to fabricate and occupies a smaller space compared to the antenna whose structure is three-dimensional. [1][2][3][4][5][6] Some design schemes for internal planar antennas of mobile phones have been presented by researchers, [7][8][9][10][11][12][13][14][15][16] but only a part of these can cover LTE/WWAN eight-band completely, and they all occupy a relatively large area. [10][11][12][13][14][15][16] A T-shape monopole antenna with a size of 17 × 58 mm 2 was presented in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that by applying a parallel‐resonant (PR) spiral slit, a small‐size planar tablet computer antenna can provide two wide operating bands to cover the 824–960 and 1710–2170 MHz for penta‐band wireless wide area network (WWAN) operation [1]. The applied PR slit generally does not increase the size of the antenna, and the wideband operation is obtained by generating a parallel resonance [2–7] at about 1.2 GHz, higher than the antenna's desired lower band, to cause a new resonance occurred inside the desired lower band and nearby the originally excited resonant mode of the antenna at about 850 MHz. This feature leads to a dual‐resonance characteristic obtained for the antenna's lower band, making it capable of wideband operation to cover the desired 824–960 MHz band with a small antenna size.…”
Section: Introductionmentioning
confidence: 99%
“…This feature leads to a dual‐resonance characteristic obtained for the antenna's lower band, making it capable of wideband operation to cover the desired 824–960 MHz band with a small antenna size. To achieve such a parallel resonance, the technique of using a band‐stop circuit which comprises a chip inductor and a chip capacitor connected in series [2–5] or using a distributed band‐stop circuit which comprises a printed shorted strip to closely couple with the antenna's main radiator [6, 7] has been applied. In the latter case, the printed shorted strip contributes an equivalent inductance to perform as a printed inductor, whereas the coupling between the shorted strip and the antenna's main radiator contributes an equivalent capacitor to perform as a printed capacitor, both the printed inductor and capacitor formed into a printed PR circuit for the antenna to generate a parallel resonance at the desired frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation